Does US aid buy UN general assembly votes? A disaggregated analysis - Axel Dreher; Peter Nunnenkamp; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2006)
Using panel data for 143 countries over the period 1973-2002, this paper empirically analyzes the influence of US aid on voting patterns in the UN General Assembly. We use disaggregated aid data to account for the fact that various forms of aid may differ in their ability to induce political support by recipients. We obtain strong evidence that US aid buys voting compliance in the Assembly. More specifically, our results suggest that general budget support and untied grants are the major aid categories by which recipients have been induced to vote in line with the United States. When replicating the analysis for other G7 donors, no comparable patterns emerge.
Keywords: F33; 330; UN General Assembly; Voting; Bilateral Aid; Bilaterale Entwicklungshilfe; Amerikanisch; Internationale Politik; Wahlverhalten; Schätzung; Welt